Political Discourse In Media Space: A Critical Discourse Perspective In Indonesia - Yunanto, Fredy; Sy, Evha Nazalatus Sa'adiyah; Kasanova, Ria (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyse political discourse in the media space in Indonesia using a critical discourse approach. The main objective of the research is to understand how political discourse is constructed, presented, and received in various types of media in Indonesia, as well as to reveal its impact on public opinion and the democratic process. Through critical discourse analysis, this research attempts to identify patterns, rhetorical strategies, and biases that may be contained in political narratives delivered by mass media. The research method involves collecting data from various media sources, such as newspapers, television, radio, and online platforms, which are then analysed using a critical discourse approach. The results reveal that the construction of political narratives in the Indonesian media is often influenced by certain political and economic interests, which reinforce framing in accordance with a particular agenda. In additionn, various rhetorical strategies, such as the use of emotional appeals, analogies, and emphasis on authority, are also used in political reporting to influence public opinion. The findings also show that political discourse in the media tends to accentuate opinion polarisation, political personalisation and stereotyping, which directly affects political participation and decision-making processes.